2011
DOI: 10.1073/pnas.1105351108
|View full text |Cite
|
Sign up to set email alerts
|

Designing super selectivity in multivalent nano-particle binding

Abstract: A key challenge in nano-science is to design ligand-coated nanoparticles that can bind selectively to surfaces that display the cognate receptors above a threshold (surface) concentration. Nanoparticles that bind monovalently to a target surface do not discriminate sharply between surfaces with high and low receptor coverage. In contrast, "multivalent" nano-particles that can bind to a larger number of ligands simultaneously, display regimes of "super selectivity" where the fraction of bound particles varies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
489
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 301 publications
(508 citation statements)
references
References 24 publications
19
489
0
Order By: Relevance
“…For example, in a Phase I clinical trial, a Tf-containing nanoparticle was used to deliver siRNA to cancer patients and shown to deliver functional siRNA to melanoma tumors in a dose-dependent manner (6). The results demonstrate that Tf-containing nanoparticles can be administered safely to humans.It is well known that the avidity and receptor selectivity of targeted nanoparticles can be tuned by the choice of targeting ligand and its number density; multivalent nanoparticles can engage multiple cell surface receptors simultaneously (7,8). When an individual targeting ligand is conjugated to a nanoparticle, the affinity of the ligand to the receptor is reduced.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a Phase I clinical trial, a Tf-containing nanoparticle was used to deliver siRNA to cancer patients and shown to deliver functional siRNA to melanoma tumors in a dose-dependent manner (6). The results demonstrate that Tf-containing nanoparticles can be administered safely to humans.It is well known that the avidity and receptor selectivity of targeted nanoparticles can be tuned by the choice of targeting ligand and its number density; multivalent nanoparticles can engage multiple cell surface receptors simultaneously (7,8). When an individual targeting ligand is conjugated to a nanoparticle, the affinity of the ligand to the receptor is reduced.…”
mentioning
confidence: 99%
“…It is well known that the avidity and receptor selectivity of targeted nanoparticles can be tuned by the choice of targeting ligand and its number density; multivalent nanoparticles can engage multiple cell surface receptors simultaneously (7,8). When an individual targeting ligand is conjugated to a nanoparticle, the affinity of the ligand to the receptor is reduced.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such selectivity can be achieved by exploiting multivalency. A series of recent experimental and theoretical papers have shown that multivalent carriers (nanoparticles or polymers) can distinguish target surfaces (cells) on the basis of their receptor concentration, rather than just on the basis of the presence of a suitable receptor (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…68 Whereas it is widely thought that problems, such as immunogenicity are chemistry dependent and might be difficult to study using the kind of coarse-grained models we discuss here (although some recent results are starting to question this assumption 70 ), other aspects of selectivity can well be captured within this modelling approach. In fact, selective targeting via functionalised nanoparticles is an area where modelling has predicted very interesting and sometimes counter-intuitive behaviours, [71][72][73] whose exploitation might be extremely useful in the design of targeting systems, as we are about to discuss.…”
Section: Controlling Nanoparticles Binding Selectivitymentioning
confidence: 99%